Caracterização dos efeitos de formulado à base de nim no desempenho de Hypothenemus hampei e aplicação em estratégias de manejo em café arábica - Escobar Padilla, José Justo (2022)
One of the main threats to the production of coffee in Brasil and in the world is the insect plague mostly known as coffee berry borer, Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae). Most coffee producers use applications of chemical insecticides as basically the only method of control. Nevertheless, a strategy that has been increasing in use in the last few years is the application of bioinsecticides; Studies have shown that bioinsecticides based on neem extracts can cause reduction in damaged fruits, higher mortality and a repellent effect on the coffee berry borer, with potential for being introduced in the management strategies for arabica coffee. The objective of this study was to evaluate the efficiency of control of the coffee berry borer in plants of arabica coffee with the use of a product based on neem extract (Openeem Plus) in strategies of integrated management with chemical and microbiological insecticides, and characterize the effects of the botanical product in terms of deterrence and development of the plague. The efficiency of the product was evaluated in applications that were isolated, in rotation or in association with other insecticides in the field, the preference and colonization of the coffee berry borer in green and red fruits was done comparing treated and non-treated grains in the laboratory and the development of the plague was studied in the laboratory using artificial diet and in traps in the fields comparing the effects of the neem treated fruits with the witness. In the field experiments, some combinations of treatments maintained the percentage of damaged fruits below the level of economic damage (10% of damaged fruits), besides the high efficiency in the reduction of larvae infestation in the fruits. In the field trials with traps, the number of eggs was higher in the witness in comparison with the neem extract. In the evaluations of preference and colonization of the coffee berry borer in green and cherry grains, there was no difference between the treatments. In the trials with application of the neem extract in artificial diet, a percentage of dishes with presence of eggs and the number of eggs was reduced by the neem extract. Considering the results obtained in the laboratory and traps in the field, there was a direct interference of the neem extract in the physiology and development of the coffee berry borer, reducing the oviposition in the exposed females, and/or a medium term deterrence effect during the feeding and oviposition in the seeds due to unpalatability caused by the neem extract. It was also demonstrated that the applications of the treatments in the precise time can increase the efficiency in control of the populations of the plague, evidenced by the significant effect of the time evaluations in the field infestations. It is concluded with these studies that the neem extract can be used in integrated pest management strategies for the coffee berry borer, with applications in rotations or mixtures with chemical and microbiological products in arabica coffee, affecting mainly the infestation of the plague by the reduction of the oviposition.